The insertion of the nurse in the psychosocial support center of (caps): - Adriano Rodrigues de Souza; Ana Roberta Vilarouca da Silva; Camilla Pontes Bezerra; Violante Augusta Batista Braga (Rev Rene)
The aim of this reflexive study was to analyze the practice of the nurse from CAPS, tracing a parallel between the experiences already related and present in the literature and the rules of Psychiatric Reformation. This reflexion was based on one of the authors’ experience reports about the personal professional practice as a nurse from a CAPS in Fortaleza-CE. It was traced a parallel with others already related and present in publications from Bireme data-bank. Taking our analysis into consideration, it was possible to ascertain the existence of difficulties for the nurse to introduce and identify their role/ function in the new services, what is probably due to the non-assimilation of the new rules about mental health attention. We also consider thata lot has to be done and transformed in the mental health practice, what demands the engagement of the various social segments in the construction of an attention net that meet the new order of emotional rules and demands.